OPTIMALISASI PENGEMBANGAN PEMUDA POSITIF MELALUI INTEGRASI LIFE SKILLS DALAM PELATIHAN DAN PEMBINAAN OLAHRAGA DESA PANGGULO - I Kadek Suardika; Arief Ibnu Haryanto; Moh. Rivai Nakoe; Mohammad Son Dadu; Husnina Datau (UNIVERSITAS PGRI MADIUN, 2025)
Abstract. Integration of life skills in sports training and coaching is a constructive response to the moral degradation of adolescents as reflected in the situation analysis in Panggulo Village, Bone Bolango Regency, Gorontalo Province. Scenario analysis identified the main causes of poor moral development of adolescents as the lack of opportunities to engage in constructive activities, modification of family structures, and uncontrolled media influence. The purpose of this program is to instill moral values ??in the next generation through family involvement, community service initiatives, and moral education. Active community participation is needed for identification, analysis, and resolution of problems in the community service method using the Participatory Action Research (PAR) approach. The understanding and application of sports values ??by adolescents increased as a result of this program, especially in the areas of teamwork, goal setting, time management, emotional intelligence, communication, social skills, leadership, problem solving, and decision making. This program successfully involved 50 adolescents from Panggulo Village, with 95% of them actively participating in training sessions and sports activities. Life skills evaluation showed significant improvements in teamwork, time management, and emotional intelligence, with an average evaluation score increasing by 40% after participating in the program. Thus, through positive sports experiences, this community service program not only improves physical components but also helps young people develop a strong moral foundation or positive youth development. Abstrak. Integrasi life skills dalam pelatihan dan pembinaan olahraga adalah respons konstruktif terhadap degradasi moral remaja yang tercermin dalam analisis situasi di Desa Panggulo, Kabupaten Bone Bolango, Provinsi Gorontalo. Analisis skenario mengidentifikasi penyebab utama buruknya pembinaan moral remaja adalah tidak adanya kesempatan untuk terlibat dalam kegiatan yang membangun, modifikasi struktur keluarga, dan pengaruh media yang tidak terkendali. Tujuan dari terciptanya program ini adalah untuk menanamkan nilai-nilai moral kepada generasi penerus melalui keterlibatan keluarga, inisiatif pengabdian kepada masyarakat, dan pendidikan moral. Partisipasi aktif masyarakat diperlukan untuk identifikasi, analisis, dan penyelesaian masalah dalam metode pengabdian kepada masyarakat yang menggunakan pendekatan Participatory Action Research (PAR). Pemahaman dan penerapan nilai-nilai olahraga oleh remaja meningkat sebagai hasil dari program ini, khususnya dalam bidang kerja sama tim, penetapan tujuan, manajemen waktu, kecerdasan emosional, komunikasi, keterampilan sosial, kepemimpinan, pemecahan masalah, dan pengambilan keputusan. Program ini berhasil melibatkan 50 remaja dari Desa Panggulo, dengan 95% di antaranya aktif berpartisipasi dalam sesi pelatihan dan kegiatan olahraga. Evaluasi life skills menunjukkan peningkatan signifikan pada kemampuan kerja sama tim, manajemen waktu, dan kecerdasan emosional, dengan rata-rata skor evaluasi meningkat sebesar 40% setelah mengikuti program. Dengan demikian, melalui pengalaman olahraga yang positif, program pengabdian masyarakat ini tidak hanya meningkatkan komponen fisik tetapi juga membantu generasi muda mengembangkan dasar moral yang kuat atau positive youth development.